Synthesis and Antibacterial and Antibiofilm Activity of Iron Oxide Glycerol Nanoparticles Obtained by Coprecipitation Method - Simona Liliana Iconaru; Alina Mihaela Prodan; Philippe Le Coustumer; Daniela Predoi (Journal of Chemistry)
The glycerol iron oxide nanoparticles (GIO-NPs) were obtained by an adapted coprecipitation method. The X-ray diffraction (XRD) studies demonstrate that GIO-NPs were indexed into the spinel cubic lattice with a lattice parameter of 0.835 nm. The refinement of XRD spectra indicated that no other phases except maghemite were detected. The adsorption of glycerol on iron oxide nanoparticles was investigated by Fourier transform infrared (FTIR) spectroscopy. On the other hand, this work implicated the use of GIO-NPs in antibacterial studies. The results indicate that, in the case of P. aeruginosa  1397 biofilms, at concentrations from 0.01 mg/mL to 0.625 mg/mL, the glycerol iron oxide inhibits the ability of this strain to develop biofilms on the inert substratum.